Effects of beryllium on microstructure and resiliency of silver-copper alloy - Chairuangsri T. (2014)
Effects of beryllium on microstructure and resiliency of cast Ag-Cu alloy containing 93.5 wt%Ag were investigated. Beryllium has an effect on modification of the eutectic structure from the typical lamellar structure to be apparently discrete Ag-rich phase encapsulated in the Cu-rich constituent. Transmission electron microscopy revealed that precipitation of fine (>20nm) fcc precipitates were observed in the dendritic areas of the Be-containing alloy after ageing heat treatment. Modulus of resilience was used to determine resiliency of the alloys. The modulus of resilience of the Be-containing alloy was about two times that of the alloy without Be addition. This is believed to relate to the precipitation of fine fcc precipitates in the dendritic areas and the modification of eutectic structure in the Be-containing alloy.